Effect of deinstitutionalisation for adults with intellectual disabilities on costs: a systematic review - Charles Normand; Mary McCarron; Esther Murphy; Peter May; Naoise Webb; Greg Sheaf; Philip McCallion; Roger Stancliffe; Valerie Smith; Richard Lombard Vance; Mary-Ann O'Donovan (BMJ Open)
Objective To review systematically the evidence on the costs and cost-effectiveness of deinstitutionalisation for adults with intellectual disabilities.Design Systematic review.Population Adults (aged 18 years and over) with intellectual disabilities.Intervention Deinstitutionalisation, that is, the move from institutional to community settings.Primary and secondary outcome measures Studies were eligible if evaluating within any cost-consequence framework (eg, cost-effectiveness analysis, cost–utility analysis) or resource use typically considered to fall within the societal viewpoint (eg, cost to payers, service-users, families and informal care costs).Search We searched MEDLINE, PsycINFO, CENTRAL, CINAHL, EconLit, Embase and Scopus to September 2017 and supplemented this with grey literature searches and handsearching of the references of the eligible studies. We assessed study quality using the Critical Appraisals Skills Programme suite of tools, excluding those judged to be of poor methodological quality.Results Two studies were included; both were cohort studies from the payer perspective of people leaving long-stay National Health Service hospitals in the UK between 1984 and 1992. One study found that deinstitutionalisation reduced costs, one study found an increase in costs.Conclusion A wide-ranging literature review found limited evidence on costs associated with deinstitutionalisation for people with intellectual disabilities. From two studies included in the review, the results were conflicting. Significant gaps in the evidence base were observable, particularly with respect to priority populations in contemporary policy: older people with intellectual disabilities and serious medical illness, and younger people with very complex needs and challenging behaviours.PROSPERO registration number CRD42018077406